2010
DOI: 10.1071/ch09456
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Relative Disulfide Energies: An Accurate Ab Initio Potential Energy Surface

Abstract: Disulfide torsional energy, a good predictor of disulfide redox potential in proteins, may be estimated by interpolation on a potential energy surface (PES) describing the twisting of diethyl disulfide through its three central dihedral angles. Here we update PES calculations at the M05-2X level of theory with the 6-31G(d) basis set. Although the surface shows no qualitative differences from an earlier MP2(full) PES, energy differences greater than 1 kJ mol–1 were seen for conformations with χ2 between –60° an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…This average value does not t the skew conformation, where the dihedral angle is close to 85 , which is known to be the most stable both experimentally [41][42][43] and theoretically. 36,[49][50][51] Any disulde linkage formed in such a compressed cis conformation would be highly energetic, as stated above. In other words, under this monolayer-like structure the formation of disulde is hindered.…”
Section: Resultsmentioning
confidence: 99%
“…This average value does not t the skew conformation, where the dihedral angle is close to 85 , which is known to be the most stable both experimentally [41][42][43] and theoretically. 36,[49][50][51] Any disulde linkage formed in such a compressed cis conformation would be highly energetic, as stated above. In other words, under this monolayer-like structure the formation of disulde is hindered.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Dependence of disulde torsional strain on embeddedness. As in previous works, 11,22,44 we assessed the strain experienced by each aCSDn in our database due to torsion around the dihedral angles of the disulde bond. In particular, we investigated the dependence of the torsional strain of the disulde on the embeddedness of the motif.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21] The number of aCSDns in protein structures in the PDB is increasing relative to other disuldes, likely due to the solution of more challenging structures that contain redox-active disuldes as technical advances in X-ray crystallography are made. 22 Several groups have investigated the properties of aCSDns found in the PDB, [23][24][25][26] focussing on the conformations adopted by the disuldes and the associated torsional strain. These investigations have consistently found that aCSDns have an extremely strong preference to adopt a right-handed staple disulde conformation.…”
Section: Introductionmentioning
confidence: 99%
“…[2] An accurate ab initio potential energy surface describing the twisting of diethyl disulfide through its three central dihedral angles is described by Haworth and coworkers. [3] Zhang and colleagues report a first-principles study of fluorination effects on atomic hydrogen interactions with fluorinated corannulene radical (C 15 H 10 F 5 ). They found that on carbon top site the adsorption is almost barrierless, whereas in the middle bond site there is a barrier for the hydrogen adsorption.…”
Section: Papers In This Issuementioning
confidence: 99%